Thin-section petrography of ceramic materials - Peterson, Sarah E. (INSTAP archaeological excavation manual, 2009)
As part of the INSTAP Archaeological Excavation Manual series, Thin-Section Petrography of Ceramic Materials provides a concise overview of the history and application of the practice while detailing how this type of petrographic analysis can benefit archaeologists in the field. When thin-section analysis is employed as part of a thorough, multi-disciplinary study of ceramic materials, it provides a wealth of additional interpretative data to archaeologists, allowing for more accurate interpretations of the past, especially regarding pottery production, provenance, variations in technology ove